Role-Play - Kraus, Rachel (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Role-play is an instructional strategy in which students act the part of another person in aparticular situation (Ladousse 1987; van Ments 1983). In these scenarios, students experience someone else’s life, choices, or dilemmas. They adopt a persona, interests, likes, and/or attitudes that tend to be different from their ordinary experiences. This adoption of an alternative identity ideally allows students to briefly see the world through the eyes of someone else. They take on these roles in an environment that is safe, which allows students to explore and use their imagination. Students do not face the risks that they may normally encounter if the situation were "real" (Ladousse 1987). Therefore, nuances and numerous aspects of a decision, position, concept, etc. can be considered without a student exposing his or her own beliefs.